Simultaneous Determination of Dimethomorph and Chlorothalonil in Pesticide Formulation: HPLC Method Development and Validation - Anum Hafeez; Sajid Iqbal; Iffat Abdul Tawab Khan; Abbas Bhutto; Faiza Anwar; Qurrat-ul-Ain (International Journal of Economic and Environmental Geology, 2018)
The identification and accurate quantification of pesticides is important to verify the recommended concentration of active content of each pesticide in formulated products to avoid adverse effects on human life due to over dosage. In this study, method of quantitative determination of Dimethomorph and Chlorothalonil in pesticide formulation was developed and validated by using ICH guidelines. Chromatographic separations with good resolution were performed on Beckman C-18 column (5 µm x 150 mm x 4.6 mm), using 80:20, v/v – (CH3CN:H2O) as mobile phase in isocratic mode at 230 nm. The retention time for Dimethomorph and Chlorothalonil at flow rate 1.2 mL/min was 6.21 and 9.63 minutes, respectively. Calibration curves of both studied fungicides (Chlorothalonil and Dimethomorph) were linear showing coefficient of determination greater than 0.996. %RSD value of inter-day precision was found to be less than 3 for both pesticides and for intra-day precision these values were less than 2. Inter laboratory comparison (ILC) method was applied to evaluate the accuracy of the proposed method and Z-score values were found to be less than 2. The proposed method is therefore efficient, accurate, and cost-effective and can suitably be used for simultaneous quantitative determination of Dimethomorph and Chlorothalonil in pesticide formulated products.